Case report: multiple systemic disseminated tuberculosis mimicking lymphoma on 18F-FDG PET/CT. Issue 29 (July 2017) - Hou, Shasha; Shen, Jie; Tan, Jian
Abstract: Rationale: 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (F-18 FDG PET/CT) has an important role in the diagnosis of various malignancies. However, F-18 FDG can also exhibit intense accumulation in tissues in inflammatory conditions such as active tuberculosis (TB) and sarcoidosis. Patient concerns: We report a case of a 52-year-old female with irritable cough. CT showed a lung mass with multiple bilateral lung nodules, and sarcoidosis was suspected. F-18 FDG PET/CT was undertaken for the diagnosis and showed intense uptake of FDG in the mass in the lower lobe of the right lung, multiple lymph nodes, liver, and spleen. The maximum standardized uptake value of F-18 FDG was 43.58. This pattern of involvement most likely represents lymphomatous involvement. Diagnoses: Histopathology suggested tubercular involvement. Intervention and outcomes: The patient received anti-TB treatment and recovered. Lessons: Abovementioned extent and distribution of F-18 FDG in tubercular lesion is relatively rare, thus, one must be observant and aware with regards to TB being a strong mimic of lymphoma in endemic regions.